The new paradigm for financial markets : the credit crisis of 2008 and what it means - Soros, George, 1930- (PublicAffairs, 2008)
In the midst of the most serious financial upheaval since the Great Depression, legendary financier George Soros explores the origins of the crisis and its implications for the future. In a concise essay that combines practical insight with philosophical depth, Soros makes an invaluable contribution to our understanding of the great credit crisis and its implications for our nation and the world.
Keywords: finanční krize -- Spojené státy americké; Spojené státy americké -- hospodářská politika